Binding contracts, non-binding promises and social feedback in the intertemporal common-pool resource game - Wojtek Przepiorka; Andreas Diekmann (Games, 2020)
In the intertemporal common-pool resource game, non-cooperative behavior produces externalities reducing subjects' payoffs in both the present and the future. In this paper, we investigate through two experiments whether binding contracts, non-binding promises and social feedback help to promote sustainable behavior. We find that cooperation is higher in groups where a contract can be signed or where subjects made a promise to cooperate throughout the experiment. However, not all groups sign the contract unanimously and subjects who made a promise adjust their cooperation downwards over time. We find no difference between the control condition without any regulation and the treatment condition in which subjects receive feedback on their past behavior in private. However, if received feedback can be learned by all group members, cooperation is significantly higher. Our findings show that non-binding promises and social feedback increase cooperation, but the former only in the short-run and the latter only if made public.
Keywords: 330; laboratory experiment; common-pool resource; cooperation; non-binding promise; social feedback